Oscar Smith journal - Smith, Oscar (Sailor)
Transcript of Smith's journal (1861 May 19-1862 December 24) kept while serving aboard the Hartford, flagship of Commodore David Glasgow Farragut, on the lower Mississippi during the Civil War. Editorial notes added by Smith's son when the journal was transcribed.
Typewritten transcript.
Sailor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Farragut, David Glasgow, -- 1801-1870.; Hartford (Ship); United States. -- Navy -- History -- Civil War, 1861-1865.; Mississippi River -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Naval operations; Sailors